Analysis of the influence of ply-orientation in delamination progression in composites laminates using the Serial/Parallel Mixing Theory. (28th July 2021) - Solis, A.; Barbero, E.; Sánchez-Sáez, S.
Abstract: In this work, an analysis on the influence of fibre-orientation in the progression of delamination was carried out. The study was focused on a cracked beam according to an End Notch Flexure test configuration. The Serial/Parallel Mixing Theory was used as the composite constitutive law along with a continuum damage model to simulate delamination. This mathematical approach was implemented in a custom-made FEM code and applied to model the delamination progression. The model was validated with two sets of experimental results from the literature involving 0° fibre-oriented laminates. After validation, a beam made of plies oriented between 0° and 90° was analysed. The model predicts the loss of stiffness and strength due to the increment of fibre angle. In addition, the stress concentration phenomenon at the crack tip and delamination onset was properly represented. The difference observed in the progression of delamination along the width of the beam highlights the need for a three-dimensional representation to model fibre-oriented beams. Graphical abstract: Image 1 Highlights: Delamination produced in a ENF test is represented using a 3D FEM model. CDM and S/PMT as constitutive law of the composite material are considered. Fibre is considered elastic while matrix can be degraded using a damage variable. Delamination onset and progression are analysed vs fibre orientation ( θ ). Slip of crack lips varies for the same level of imposed displacement with θ .